ANALISIS LAPORAN KEUANGAN PT. SMARTFREN TELECOM TBK PRA DAN PASCA AKUISISI - Kaparang, Stevani Fransy Gillis; Poputra, Agus Tony (Universitas Sam Ratulangi, 2013)
The rapid development of telecomunications industry has changed people’s views of the services communications. This is challenge for telecommunication providers so they must perform a variety ways that makes their company still exist in this industry. One way to do is by restructuring through acquisitions.This research aims is to analyzing the financial performance of PT. Smartfren Telecom Tbk pre and post acquisition. Data used in this research is secondary data that the company’s financial statement in 2010-2011. Method of analysis used in is financial ratio analysis such as liquidity ratio, leverage ratio, asset management ratio, and profitability ratio.The research find that financial performance of PT. Smartfren Telecom Tbk shows the positive impact that can be seen from: ( i ) level of liquidity and profitability has improved to the post acquisition, ( ii ) level of leverage has improved because until 2011 experienced a significant decline, ( iii ) level of assets management is not good because it has decreased in 2011. Thus it can be concluded that the decision to carry out the acquisition demonstrate a positive impact for the company.